(untitled) (Modern education and development, 2025)
The article notes that today the Turing test has undergone several modifications and is used to evaluate many systems, including chatbots and virtual assistants. It is noted that the use of the Turing test in the development of artificial intelligence and its capabilities relative to humans is important not only in scientific research, but also in the field of information technology, in practical testing of artificial intelligence and the creation of real-life systems.